Disordered eating among preadolescent boys and girls: the relationship with child and maternal variables - Gonçalves, Sónia (2012)
Objective: (1) To analyze the eating behaviors and body satisfaction of boys and girls and to examine their mothers’ perceptions of these two domains, and (2) To evaluate eating problem predictors using child body mass index (BMI), self-esteem, and body satisfaction as well as maternal BMI, eating problems, and satisfaction with their child’s body. The participants included 111 children (54.1% girls aged between 9-12 years old) and their mothers. Assessment measures included the Child Eating Attitude Test, the Self-Perception Profile for Children, the Eating Disorders Questionnaire, and the Child Eating Behavior Questionnaire. Child and maternal measures also included BMI and Collins Figure Drawings. Results: i) no association between child and maternal BMI for either sex was found; ii) no difference was found between boys and girls with regard to eating behavior; iii) most children revealed a preference for an ideal body image over their actual body image; iv) most mothers preferred thinner bodies for their children; v) greater BMI was related to higher body dissatisfaction; and vi) child BMI and dissatisfaction with body image predicted eating disturbances in boys, whereas self-esteem, maternal BMI, and eating behavior predicted them in girls. Discussion: Maternal eating problems and BMI were related to female eating problems only.